The Homophily of Teachers and Religious Intolerance: A Study of Two High Schools in Pisang Batu City, Indonesia - Chamidi, Nicky Chairani Isa (UI Scholars Hub, 2020)
Religious intolerance is worsening in various countries, including in Indonesia, a country with the largest Muslim population in the world. In Indonesia, one of the actors of this phenomenon is teachers. According to several studies, it was caused by state policies, religious education, learning strategy and teacher’s capacity. Based on the cases in two high schools in Pisang Batu1City in Indonesia, this study discovered similar findings. However, it was caused not only by the factors explained in the studies mentioned, but also by homophily in social networks. The community in which the teachers were raised, their school background, friendships in the workplace and the religious groups they participate in, all showed a tendency of homogeneity, which became the basis of the growth of intolerance on the basis of religion among teachers. Keywords: teacher, religious intolerance, homophily, Indonesia